Mental rotation with colored cube figures - Rahe, Martina; Weigelt, Matthias; Jansen, Petra (Consciousness and Cognition)
Keywords: Arts and Humanities (miscellaneous); Developmental and Educational Psychology; Experimental and Cognitive Psychology

COVID-19 in German Competitive Sports: Protocol for a Prospective Multicenter Cohort Study (CoSmo-S). - Niess, AM; Widmann, M; Gaidai, R; Gölz, C; Schubert, I; Castillo, K; Sachs, JP; Bizjak, D; Vollrath, S; Wimbauer, F; Vogel, A; Keller, K; et al. (Int J Public Health)

Video analysis of 100 matches in male semi-professional football reveals a heading rate of 5.7 headings per field player and match. - Weber, J; Ernstberger, A; Reinsberger, Claus; Popp, D; Nerlich, M; Alt, V; Krutsch, W (BMC Sports Sci Med Rehabil)

Classification characteristics of fine motor experts based on electroencephalographic and force tracking data. - Gaidai, R; Goelz, C; Mora, K; Rudisch, J; Reuter, EM; Godde, B; Reinsberger, Claus; Voelcker-Rehage, C; Vieluf, S (Brain Res)

Heading and risk of injury situations for the head in professional German football: a video analysis of over 150,000 headers in 110,000 match minutes. - Weber, J; Reinsberger, Claus; Krutsch, V; Seiffert, R; Huber, L; Alt, V; Krutsch, W (Sci Med Footb)

Fitness, performance, and cardiac autonomic responses to exercise in people with epilepsy. - van den Bongard, F; Coenen, J; Reinsberger, Claus (Epilepsy Behav)

High revision arthroscopy rate after ACL reconstruction in men's professional team sports. - Bloch, H; Reinsberger, Claus; Klein, C; Luig, P; Krutsch, W (Knee Surg Sports Traumatol Arthrosc)

Sportneurologie - Reinsberger, Claus (Repetitorium Sportmedizin)

Continuous table tennis is associated with processing in frontal brain areas: an EEG approach - Visser, Anton; Büchel, Daniel; Lehmann, Tim; Baumeister, Jochen (Experimental Brain Research)
Abstract Coordinative challenging exercises in changing environments referred to as open-skill exercises seem to be beneficial on cognitive function. Although electroencephalographic research allows to investigate changes in cortical processing during movement, information about cortical dynamics during open-skill exercise is lacking. Therefore, the present study examines frontal brain activation during table tennis as an open-skill exercise compared to cycling exercise and a cognitive task. 21 healthy young adults conducted three blocks of table tennis, cycling and n-back task. Throughout the experiment, cortical activity was measured using 64-channel EEG system connected to a wireless amplifier. Cortical activity was analyzed calculating theta power (4–7.5 Hz) in frontocentral clusters revealed from independent component analysis. Repeated measures ANOVA was used to identify within subject differences between conditions (table tennis, cycling, n-back; p < .05). ANOVA revealed main-effects of condition on theta power in frontal ( p < .01, η p 2 = 0.35) and frontocentral ( p < .01, η p 2 = 0.39) brain areas. Post-hoc tests revealed increased theta power in table tennis compared to cycling in frontal brain areas ( p < .05, d = 1.42). In frontocentral brain areas, theta power was significant higher in table tennis compared to cycling ( p < .01, d = 1.03) and table tennis compared to the cognitive task ( p < .01, d = 1.06). Increases in theta power during continuous table tennis may reflect the increased demands in perception and processing of environmental stimuli during open-skill exercise. This study provides important insights that support the beneficial effect of open-skill exercise on brain function and suggest that using open-skill exercise may serve as an intervention to induce activation of the frontal cortex.
Keywords: General Neuroscience

Surface Instability Modulates Cortical Information Processing In Multi-Joint Compound Movements - Lehmann, Tim; Visser, Anton; Havers, Tim; Büchel, Daniel; Baumeister, Jochen (Medicine & Science in Sports & Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Effects of surface instability on cortical information processing during multi- joint compound movements: an exploratory EEG study - Lehmann, Tim; Visser, Anton; Havers, Tim; Büchel, Daniel; Baumeister, Jochen

Performance and Brain Activity in Older Adults while Playing Leaning and Stepping Exergames - Müller, Helen Martha; Skjæret-Maroni, Nina; Vereijken, Beatrix; Baumeister, Jochen

Changes In Eeg Microstate Patterns Following Exhaustive Treadmill Exercise When Employing Reduced Channel Resolution - Büchel, Daniel; Allen, Carlos; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Medicine & Science in Sports & Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Ecological validity in exercise neuroscience research: A systematic investigation - Chang, Melissa; Büchel, Daniel; Reinecke, Kirsten; Lehmann, Tim; Baumeister, Jochen (European Journal of Neuroscience)
Keywords: General Neuroscience

Motorische Kompetenzen im Kindesalter: Monitoring, Intervention und Zusammenhänge mit der Selbstwahrnehmung - Strotmeyer, Anne
Motorische Kompetenzen und die Selbstwahrnehmung dieser sind zentral hinsichtlich der Ausbildung eines gesundheitsförderlichen Lebensstils. Bewegungsmangel im Kindesalter und motorische Defizite unterstreichen die Relevanz von Untersuchungen in diesem Forschungsfeld. In diesem Kontext besteht Forschungsbedarf, welcher an der jungen Forschungslinie zu motorischen Basiskompetenzen ansetzt. Daher zielt die vorliegende Arbeit auf die Untersuchung motorischer Basiskompetenzen im Kontext des Monitorings, der Intervention sowie der Untersuchung von Zusammenhängen mit der Selbstwahrnehmung. Es wurden konfirmatorische Faktorenanalysen durchgeführt sowie eine kompetenzorientierte Intervention für das mittlere Kindesalter konzipiert und evaluiert. Zudem fanden Varianzanalysen mit Messwiederholung und manifeste Pfadmodelle Anwendung. Neben der Bestätigung der faktoriellen Struktur des Tests zur Erfassung motorischer Basiskompetenzen (MOBAK 3-4), wurden Zusammenhänge mit endogenen sowie exogenen Faktoren nachgewiesen. Es konnte gezeigt werden, dass mit Hilfe der relativ kurzen Intervention positive Effekte auf die motorischen Basiskompetenzen erzielt werden können. Zudem zeigten sich moderate Korrelationen zwischen motorischen Basiskompetenzen und der Selbstwahrnehmung. Auf Grundlage dieser Befunde sollten im Bereich der Objektkontrolle vor allem motorische Kompetenzen und im Bereich der Lokomotion insbesondere die Selbstwahrnehmung zur Steigerung des Kompetenzlevels gefördert werden.

COVID-19 in German Competitive Sports: Protocol for a Prospective Multicenter Cohort Study (CoSmo-S) - Niess, Andreas Michael; Widmann, Manuel; Gaidai, Roman; Gölz, Christian Johannes; Schubert, Isabel; Castillo, Katty; Sachs, Jan Philipp; Bizjak, Daniel; Vollrath, Shirin; Wimbauer, Fritz; Vogel, Azin; Keller, Karsten; et al. (International Journal of Public Health)
Objective: It is unclear whether and to what extent COVID-19 infection poses health risks and a chronic impairment of performance in athletes. Identification of individual health risk is an important decision-making basis for managing the pandemic risk of infection with SARS-CoV-2 in sports and return to play (RTP). Methods: This study aims 1) to analyze the longitudinal rate of seroprevalence of SARS-CoV-2 in German athletes, 2) to assess health-related consequences in athletes infected with SARS-CoV-2, and 3) to reveal effects of the COVID-19 pandemic in general and of a cleared SARS-CoV-2 infection on exercise performance. CoSmo-S is a prospective observational multicenter study establishing two cohorts: 1) athletes diagnosed positive for COVID-19 (cohort 1) and 2) federal squad athletes who perform their annual sports medical preparticipation screening (cohort 2). Comprehensive diagnostics including physical examination, laboratory blood analyses and blood biobanking, resting and exercise electrocardiogram (ECG), echocardiography, spirometry and exercise testing added by questionnaires are conducted at baseline and follow-up. Results and Conclusion: We expect that the results obtained, will allow us to formulate recommendations regarding RTP on a more evidence-based level.
Keywords: Public Health; Environmental and Occupational Health; Health (social science)

Stimulating performance: A scoping review on transcranial electrical stimulation effects on olympic sports - Friehs, Maximilian A.; Whelan, Eric; Güldenpenning, Iris; Krause, Daniel; Weigelt, Matthias (Psychology of Sport and Exercise)
Keywords: Applied Psychology

Valence-dependent neural correlates of augmented feedback processing in extensive motor sequence learning – Part II: Predictive value of event-related potentials for behavioral adaptation and learning - Margraf, Linda; Krause, Daniel; Weigelt, Matthias (Neuroscience)
Keywords: General Neuroscience

Valence-dependent Neural Correlates of Augmented Feedback Processing in Extensive Motor Sequence Learning – Part I: Practice-related Changes of Feedback Processing - Margraf, Linda; Krause, Daniel; Weigelt, Matthias (Neuroscience)
Keywords: General Neuroscience

Repeating head fakes in basketball: Temporal aspects affect the congruency sequence effect and the size of the head-fake effect. - Polzien, Andrea; Güldenpenning, Iris; Weigelt, Matthias (Journal of Experimental Psychology: Applied)
Keywords: Experimental and Cognitive Psychology